The metabolic syndrome identifies a heterogeneous group of metabolic component combinations in the Asia-Pacific region - Lee, Crystal; Huxley, Rachel; Woodward, M.; Zimmet, P.; Shaw, J.; Cho, N.; Kim, H.; Viali, S.; Tominaga, M.; Vistisen, D.; Borch-Johnsen, K.; Colagiuri, S. (Elsevier Ireland Ltd, 2008)
Aim: To compare the prevalence of metabolic syndrome (MetS) by combinations of MetS components derived from the National Cholesterol Education Program Adult Treatment Panel III (ATPIII) and International Diabetes Federation (IDF) definitions. Methods: Four studies with ethnically distinct populations from the Asia-Pacific region were selected from the DETECT-2 study database. The prevalences of combinations of MetS components using the modified ATPIII (modATPIII) and IDF MetS definitions were compared between sexes and across populations. Results: A total of 22,952 participants from Australia, Japan, Korea and Samoa were included. The age-adjusted prevalence of modATPIII MetS varied from 9.4 to 35.8% in men and 10.3 to 57.2% in women; results for IDF were generally higher. Prevalences of the 16 possible MetS component combinations from the modATPIII definition that result in a diagnosis of MetS ranged from 0 to 12.7%. Of those with IDF-defined abdominal obesity, the prevalences of the 11 IDF-defined MetS component combinations ranged from 0.2 to 18.3%. Conclusions: The large variation in the prevalence of possible MetS component combinations to diagnose MetS may explain the different risk of cardiovascular outcomes associated with MetS in different populations, especially since particular combinations of MetS components are associated with different risk of cardiovascular disease. © 2008 Elsevier Ireland Ltd. All rights reserved.